Development and Characterization of a Micromagnetic Alternative to Cochlear Implant Electrode Arrays - Ressa Reneth S. Sarreal; David T. Blake; Pamela T. Bhatti (IEEE, 2022)
To stimulate the auditory nerve, cochlear implants directly inject electrical current into surrounding tissue via an implanted electrode array. While many cochlear implant users achieve strong speech perception scores, there remains significant variability. Since cochlear implant electrode arrays are surrounded by a conductive fluid, perilymph, a spread of excitation occurs. The functionality of the cochlea is spatially dependent, and a wider area of excitation negatively affects the hearing of the user. Importantly, magnetic fields are unaffected by the material properties of biological components. To utilize the electromagnetic properties of the human ear, a microcoil array was developed. The microcoils are 4-turn solenoids with a 250- $μ \text{m}$ turn radius and a 31.75- $μ \text{m}$ wire radius, coated with Parylene-C. The efficient design was implemented to accelerate testing. The obtained results describe stimulation capabilities. Functionality was validated using a frequency response analyzer to measure how the generated electromagnetic power radiates in space. 99.8% power loss was observed over a 100- $μ \text{m}$ separation between a pair of identical microcoils. Obtained through finite-element modeling, the microcoils can be driven by a 60 mA, 5 kHz, sinusoidal input for 10 minutes before predicted inflammation. Rattay’s activating function was calculated to evaluate the magnetic stimulation effect of external fields on target neurons. Combined with the frequency response analysis, magnitude and spatial effects of the generated potential is established. As a result, each microcoil requires a 400- $μ \text{m}$ -wide area for each independent stimulation channel, which is 84% narrower than a commercial cochlear array channel, thereby suggesting greater spatial selectivity.